Design of complementary class-c oscillator with tail current source feedback and noise suppression for wireless applications / Pravinah Nair Shasidharan - Pravinah Nair, Shasidharan (2019)
The performance of low-powered transceivers are required to meet stringent specifications for an advanced wireless radio application. It is critical for a voltage-controlled oscillator (VCO) to meet multi-standard and multiband operation with low-power consumption and sufficient gain. This paper propose a novel technique for wide tuning range performance in a complementary class-C VCO employing a capacitive-source degeneration (CSD) to meet multi-standard operation for low-power transceivers. The technique which employs two sets of symmetrical split PMOS biased current source operating in subthreshold region achieves the desired low phase noise (PN) performance of below -120 dB/Hz at a tuning range of 2.2-to-2.9 GHz with a supply headroom of 1.2 V. The control of the dc bias point reduces the conduction angle which improves the current efficiency, power consumption and PN. Concurrently, an auxiliary ï¿½gm NMOS only class-B oscillator is incorporated to mitigate the start-up issue of the class-C VCO. At the center frequency of 2.45 GHz, the proposed VCO consumes a power of 1.73 mW, achieves a phase noise of -120 dBc/Hz at 1 MHz offset, and a figure - of - merit (FoM) of 185.41 dBc/Hz at 1 MHz. The total active chip area is only of 0.3-mm2 excluding bond pads. The proposed VCO serves as a promising solution for low-power wireless communication systems.